2002
DOI: 10.1097/00001756-200211150-00014
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of breast cancer resistance protein in microvessel endothelium of human brain

Abstract: Movement of substrates between blood and brain is known to be influenced by P-glycoprotein (P-gp) at the luminal surface of the endothelium lining brain microvessels and by multidrug resistance associated protein 1 (MRP1) at the basolateral surface of the choroid plexus epithelium. Here, using RT-PCR and Western blotting, we investigate other ABC transporters in both normal and tumour human brain tissue and demonstrate the presence of breast cancer resistance protein (BCRP). Immunofluorescence confocal microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
233
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(249 citation statements)
references
References 15 publications
15
233
0
1
Order By: Relevance
“…Further analysis revealed that the porcine BCRP was expressed in brain tissue in vivo and was predominantly localized within the endothelial cells isolated from brain capillaries. The presence of BCRP in the luminal surface of the endothelium of human brain microvessels was recently demonstrated by immunofluorescence confocal microscopy (Cooray et al, 2002). This suggests that BCRP, like Pgp and MRP1, contributes to the blood-brain barrier.…”
Section: Expression Of Bcrp In Normal Tissuesmentioning
confidence: 85%
“…Further analysis revealed that the porcine BCRP was expressed in brain tissue in vivo and was predominantly localized within the endothelial cells isolated from brain capillaries. The presence of BCRP in the luminal surface of the endothelium of human brain microvessels was recently demonstrated by immunofluorescence confocal microscopy (Cooray et al, 2002). This suggests that BCRP, like Pgp and MRP1, contributes to the blood-brain barrier.…”
Section: Expression Of Bcrp In Normal Tissuesmentioning
confidence: 85%
“…Multidrug resistance-associated proteins (MRPs), transporting conjugated metabolites such as glutathione-and glucuronideconjugates (Loe et al 1996;Kusuhara et al 1998), are expressed and localized on the basal membrane of testis Sertolli cells and the basolateral membrane of lung epithelial cells (Wijnholds et al 1998;Wright et al 1998) but no expression of MRPs was detected on isolated human brain capillaries (Seetharaman et al 1998) and no significant staining was found in mouse brain (Wijnholds et al 2000). Breast Cancer Related Protein (BCRP) is located at the BBB, mainly at the luminal surface of microvessel endothelium (Cooray et al 2002). The preferential binding of EM-1 and EM-2 on the basolateral membrane in our polarized cell model suggests an efflux transporter located on the abluminal side of the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of integrin β1 expression were decreased in SAC group, and the lowest levels were seen in the NAC population. ABCG2 mRNA, a newly proposed stem cell marker (Cooray et al, 2002;Scharenberg et al, 2002;Zhou et al, 2001) was expressed at the highest level by the RAC group, while ALL cells and SAC population expressed much lower levels of ABCG2 mRNA, with undetectable expression by the NAC population (Fig. 5B).…”
Section: Rapidly Adherent Cells Express the Highest Levels Of Integrimentioning
confidence: 95%